A NEW APPROACH FOR WATER ALLOCATION SCHEDULING IN IRRIGATION OPEN CHANNELS CASE STUDY: ALMANNA MAIN CANAL, AND ITS BRANCHES - Tarek Abuzeid; Mahmoud Sabery (JES: Journal of Engineering Sciences, 2021)
In Egypt, the Agriculture sector consumes about 85.90% of the total actual consumption of water. With population growth, expansion of economic and industrial activities and entry of Egypt into the stage of water poverty, rationalization of the consumption of irrigation water has become an urgent requirement and a key factor in achieving sustainable water development. Although crops may need different water quantities during their growth stages, irrigation canals are constantly supplied with almost the same monthly discharge during periods of peak or minimum requirements. The objective of this study is to activate a new approach for the reasonable management of the irrigation network for the study area. This approach allows the canals network to be supplied with monthly discharges consistent with the actual water consumption of the cultivated plant. Also, it helps in rationalizing consumption during the agricultural season. The new approach was applied to Almanna main canal and its branches which belong to the Assiut governorate in Egypt, as an example of the irrigation system in Egypt. Rotational distribution is practiced at the distributary canal level. The results indicated that applying the new approach on Almanna distributary canals can save a large amount of irrigation water that reaches about 19.375 Million cubic meters monthly, representing 48.68% of all irrigation water given to Almanna distributary canals. Also, the percentage value of the new discharges of Almanna distributary canals, which calculated according to the water needs of crops cultivated in the area, ranged between 32 and 67% of the designed discharges.